Seismic performance of asymmetric building structures - Zhang, Chunwei, (Civil Engineer); Alam, Zeshan; Sun, Li; Samali, Bijan (Boca Raton : CRC Press, 2020)
"This book presents detailed investigations on the effective assessment of structural seismic response under excessive torsional vibrations, demonstrating behavioural aspects from a local response perspective to global seismic demands. The work provides comprehensive analytical, computational, experimental investigations, and proposes improved design guidelines that structural engineers can utilize to enhance the seismic design of asymmetric building structures. Seismic Performance of Asymmetric Building Structures combines extensive experimental and numerical data for seismic performance assessment with a particular focus on asymmetric building structures, and includes an overview of asymmetric building structures from a seismic damage perspective local and global performance assessment of asymmetric structures under extreme seismic actions Post-earthquake damage evaluation from varying frequency trends extended numerical applications for experimental response validations evaluation of critical regions of asymmetric structures with stress concentration Statistical distribution of seismic response under varying design parameters design guidelines for asymmetric building structures This book is highly recommended for its comprehensive evaluations that have been carried out with modern sensing techniques planned with meticulous attention to cover its objectives with a particular focus on asymmetry in reinforced concrete and steel structures. It includes assessment of various aspects of asymmetric building structures that can rarely be found in the current literature. It gathers fruitful information from various building design codes and explains their limitations in addressing damage-related challenges, which is useful not only for practicing engineers but also for the research community. This book covers extensive features of asymmetric building structures and effective design guidelines comprehensively and in detail. As such, it will be invaluable for experts, researchers, students, and practitioners in various relevant fields, as well as for emergency preparedness managers"--
OCLC-licensed vendor bibliographic record.
Keywords: Earthquake resistant design -- Evaluation; TECHNOLOGY / Construction / Estimating